Model membangunkan budaya keselamatan dalam firma pembinaan di Malaysia - Misnan, Mohd. Saidin (2009)
The nature of most accidents at the construction sites shows that the construction industry is unique, involving human behaviour, dangerous construction sites, unsafe safety culture, dangerous machineries and equipments being used and implementation of various sets of procedures. Therefore, this study is carried out to achieve four objectives namely to identify factors influencing the development of safety culture, to identify the best practice for each factor in the development of safety culture, to identify the level of implementation to these factors to the development of safety culture, and to develop model for the process of implementation of best practices in the development of safety culture in construction firms. Respondents consisted 287 construction firms Grade G7 in Klang Valley, 107 Safety and Health Officer (SHO) and 15 occupational safety and health experts. The study was carried out in four stages which were stage 1 - questionnaire survey, stage 2 - questionnaire survey and interview, stage 3 - questionnaire survey and stage 4 - benchmarking, development of Data Flow Diagram (DFD) Model, validation of model and ‘Focus Group’. Data gathered from the study had been analyzed through qualitative and quantitative approaches involving coefficient analytical method Alpha Cronbach, frequency analysis, mean analysis and contents analysis. Data Flow Diagram (DFD) Model has been choosen to develop the process model of best practice implementation of safety culture development in construction firms. The study has identified nine factors influencing safety culture development in construction firms, namely leadership, involvement, recognition and acknowledgement, training and education, communication, motivation, team-work and group work, Health and Safety Committee and policy and safety planning. Leadership factor was identified as the main element that influence the best practice implementation of safety culture development in construction firms followed by involvement and training and education. Leadership was identified as the most factor of implementation, followed by policy and safety planning, and Health and Safety Committee. Meanwhile, 36 best practices had been identified in safety culture development process. Model of best practices implementation process for safety culture development in construction firms was developed using Data Flow Diagram model (DFD), whereby the development process was based on the leadership training among Safety and Health Officer (SHO). Moreover Safety and Health Officer is a competent personnel in safety aspect in construction firms and as a key to the development of safety culture.